Hysteresis response of nonlinear flutter of a truss girder: Experimental investigations and theoretical predictions. (1st October 2020) - Wu, Bo; Wang, Qi; Liao, Haili; Mei, Hanyu
Highlights: Nonlinear flutter with hysteresis effects of a bridge deck was studied. Inner mechanism of the hysteresis effects was interpreted. Nonlinear mathematical models were proposed to predict the flutter responses. An approach is proposed to identify the nondimensional aerodynamic parameters. Abstract: Nonlinear flutter response with hysteresis loop characteristics is a special aerodynamic instability phenomenon, and is of great importance and of practical interest to long span bridge designs. This paper presents a comprehensive study on nonlinear flutter of a bridge deck that has hysteresis loop characteristics over a range of wind speeds close to the flutter onset speed, using a section model wind tunnel test and theoretical analyses. The evolutions of the hysteresis loop in both the single degree of freedom (SDOF) system in torsion and the 2 degrees of freedom (2DOF) system in the vertical direction and in torsion are studied. The formation mechanism of the hysteresis loop is discussed using the equivalent total damping as a function of vibration amplitude. Two nonlinear mathematical models for the SDOF and the 2DOF systems are proposed to predict the nonlinear flutter responses, in which both the structural and aerodynamic damping are expressed as functions of time-varying displacements. An approach is proposed to identify the aerodynamic parameters based on the displacement time histories using a harmonic balancing technique. Using the identified aerodynamic parameters, a distinct dynamic system with the same section was used to validate the accuracy of the proposed models.